2022
DOI: 10.1371/journal.ppat.1010629
|View full text |Cite
|
Sign up to set email alerts
|

Near-native state imaging by cryo-soft-X-ray tomography reveals remodelling of multiple cellular organelles during HSV-1 infection

Abstract: Herpes simplex virus-1 (HSV-1) is a large, enveloped DNA virus and its assembly in the cell is a complex multi-step process during which viral particles interact with numerous cellular compartments such as the nucleus and organelles of the secretory pathway. Transmission electron microscopy and fluorescence microscopy are commonly used to study HSV-1 infection. However, 2D imaging limits our understanding of the 3D geometric changes to cellular compartments that accompany infection and sample processing can in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 110 publications
3
9
0
Order By: Relevance
“…7a). This is supported by a recent soft X-ray microscopy study also showing that HSV-1 infection leads to mitochondrial elongation 28 . Elongation has previously been observed in the dengue virus infection, in which mitochondrial fusion is induced by the inactivation of mitochondrial fission protein, dynamin-related protein 1 (DRP1) 61 .…”
Section: Discussionsupporting
confidence: 57%
“…7a). This is supported by a recent soft X-ray microscopy study also showing that HSV-1 infection leads to mitochondrial elongation 28 . Elongation has previously been observed in the dengue virus infection, in which mitochondrial fusion is induced by the inactivation of mitochondrial fission protein, dynamin-related protein 1 (DRP1) 61 .…”
Section: Discussionsupporting
confidence: 57%
“…Human herpesviruses belong to the family Herpesviridae . Herpes simplex virus 1 (HSV-1) (genus Alphaherpesviruse ), residing in sensory neurons or sympathetic neurons, has been shown to severely modify infected cells and to remodel the composition and architecture of cellular membranes [ 35 , 95 , 96 ]. One of the HSV-1 proteins, phosphatase adaptor UL21, mediates dephosphorylation and accelerates the rate of ceramide to sphingomyelin conversion, altering cell membranes and influencing viral replication [ 35 ].…”
Section: Application Of Af2 For Research On Eukaryotic Virusesmentioning
confidence: 99%
“…Though compacted chromatin restricts viral capsid diffusion, SXT imaging showed the presence of interchromatin channels, which enable capsids to reach the nuclear envelope [27]. In addition, recent SXT studies on the remodeling of cytoplasm upon HSV-1 infection have shown active dynamics of cytoplasmic vesicles, lipid droplets, and elongation of mitochondria [28]. Thus far, spatiotemporal imaging of HSV-1 infections at the entire cell level over the course of infection has been limited.…”
Section: Introductionmentioning
confidence: 99%